An Implementation of Cloudflare's Zero Trust Network Access at PT FHI - Febriyan, Rizky; Yuliadi, Boy (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
The increasing vulnerabilities of modern enterprise network security systems highlight the necessity of adopting a more comprehensive and adaptive security approach than traditional VPN infrastructures. This study explores the design and implementation of Zero Trust Network Access (ZTNA) using the Cloudflare platform at PT FHI, focusing on addressing the weaknesses caused by uncontrolled remote access and legacy security models. The research adopts an experimental methodology based on the Network Development Life Cycle (NDLC), which includes systematic phases such as needs analysis, architectural design, system implementation, testing, and performance evaluation. Data were collected through structured interviews with IT managers and security specialists, direct observation of network logs, and comprehensive testing involving three different categories of end users. The findings demonstrate significant improvements in role-based access control, granular authentication, and the elimination of unrestricted access to internal resources. Additionally, real-time monitoring and alerting features available through the Cloudflare dashboard enhance visibility and responsiveness to potential threats. The implemented system successfully applies the “never trust, always verify” principle by blocking unauthorized access attempts, enforcing continuous validation, and producing detailed audit logs. Performance evaluation results confirm stable connections, acceptable latency for critical business applications, and an overall improvement in network security posture while maintaining operational productivity across departments..